Mathematical methods for the analysis of propagation in multitrajectory in communications move - Delphin, Delphin Kabey Mwinken (2020)
A study about movable communication using the cellular technology and a mathematical model is presented. The aim of the present paper is to solve the problems of multi-trajectory propagation in the movable communications so that at least a station can have access to a point of the area (Huambo) with a sign, at the level stipulated by the communication companies, depending on the user’s need that allows a quality communication The Mathematics methods used have as objective to facilitate the search and selection of the most appropriate alternative to the case under study, and they help to take into account several aspects involved in the decision making. The objective of the methodology presented is to obtain the parameters of quality of the service needed. The introduction of an empiric model allows reducing the values of those parameters to discover the areas of the city that possess potential covering. Besides the potency prediction (through the proposed model), a study of forecast of the parameters of service quality was accomplished, the values limits of those parameters depended on the service that is being used.